Incisional hernia repair - Bhattarai, A; Bhandari, RS (Journal of Institute of Medicine Nepal, 2010)
Introduction: Incisional hernia is a late complication of any abdominal surgery, including both laparotomy and laparoscopic. It occurs at the site of previous incision through weak scar. Hernia occurs as a result of excessive tension and inadequate healing of previous incision which is often associated with surgical site infection or severe bouts of coughing in the early post operative period or injury to the nerve supplying the abdominal wall. This study was performed with objectives to review clinical profile and management of incisional hernia in Tribhuvan University Teaching Hospital (TUTH). Methods: A retrospective study was conducted at TUTH, over the period of 18 month from, Jan 2007 to June 2008. All patients with a history of abdominal surgery with a complaint of swelling over previous incision site were included in this study. Results: Twenty two patients who had undergone hernia repair during the period were included. Mean age of presentation was 47 years with the range of 27 to 80 year. Among them 17 were female and five were male. Among 17 female patients, 15 had history of laparotomy through lower midline incision and two had history of minilaparotomy for tubal ligation. Eleven patients had symptoms less than five years and 11 had more than five years. For 18 cases mesh repair was done while herniorraphy was performed in 4 cases. No complications were observed during one year follow up. Conclusions: Incisional hernia is more common in females after lower midline abdominal surgery. Mesh repair is the ideal recommended treatment except in very small incisional hernia where primary repair can be done. DOI: http://dx.doi.org/10.3126/joim.v32i1.4000 Journal of Institute of Medicine, April, 2010; 32:1 pp.34-36